Are goblet cell carcinoids a group of heterogeneous tumors? - Macak, Jirka; Nemejcova, Kristina; Dvorackova, Jana (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2017)
BACKGROUND: Goblet cell carcinoids belong to neuroendocrine tumors, according to the WHO classification. The tumors are diagnosed based on a typical histological pattern and using neuroendocrine markers. However, some tumors do not react with these markers and yet expression of proliferative markers is high. Do these tumors belong to G1 and G2 neuroendocrine tumors? METHODS: The sample comprised nine cases of tumors of the appendix identified by immunohistological methods as goblet cell carcinoids or adenocarcinoma ex goblet cell carcinoid. RESULTS: In six cases, hematoxylin and eosin staining revealed tumors completely or 90% made of characteristic large tumor cells observed in typical goblet cell carcinoids. The remaining three cases were identified as adenocarcinomas arising ex goblet cell carcinoids. Immunohistological examination revealed that in four cases of typical goblet cell carcinoids, expression of neuroendocrine markers was low or completely negative. Yet in two cases, the Ki-67 proliferative index exceeded the 20% cut-off for inclusion in the G1 and G2 category. CONCLUSIONS: Goblet cell carcinoids are a heterogeneous group of tumors that may express neuroendocrine markers in a small number of tumor cells or are negative to these markers. However, high expression of the proliferative marker Ki-67 exceeds the criteria for G1 and G2 neuroendocrine tumors. It is our opinion that these tumors may be classified as a specific type of carcinoma.
Keywords: antigen Ki-67; Female; ženské pohlaví; nádory apendixu; Immunohistochemistry; lidé; goblet cell carcinoid; World Health Organization; apendektomie; imunohistochemie; karcinoid; Světová zdravotnická organizace; negative neuroendocrine markers; Adenocarcinoma; Male; nádorové biomarkery; Aged; adenokarcinom; Neuroendocrine Tumors; Ki-67 Antigen; Biomarkers, Tumor; lidé středního věku; Appendectomy; Appendiceal Neoplasms; senioři; mužské pohlaví; appendix; Middle Aged; immunohistology; Carcinoid Tumor; neuroendokrinní nádory; Humans